2018
DOI: 10.1002/stem.2777
|View full text |Cite
|
Sign up to set email alerts
|

Poly(Lactide-Co-Glycolide)-Monomethoxy-Poly-(Polyethylene Glycol) Nanoparticles Loaded with Melatonin Protect Adipose-Derived Stem Cells Transplanted in Infarcted Heart Tissue

Abstract: Stem cell transplantation is a promising therapeutic strategy for myocardial infarction. However, transplanted cells face low survival rates due to oxidative stress and the inflammatory microenvironment in ischemic heart tissue. Melatonin has been used as a powerful endogenous antioxidant to protect cells from oxidative injury. However, melatonin cannot play a long-lasting effect against the hostile microenvironment. Nano drug delivery carriers have the ability to protect the loaded drug from degradation in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Previous studies have suggested that antioxidant pretreatment could improve cell survival and enhance ADSC therapeutic effects for myocardial infarction [19,20]. In addition, it has also been suggested that antioxidant preconditioning could preserve stemness of mesenchymal stem cells [21, trypsin-EDTA (Gibco, USA) and passaged at a ratio of 1:3.…”
mentioning
confidence: 99%
“…Previous studies have suggested that antioxidant pretreatment could improve cell survival and enhance ADSC therapeutic effects for myocardial infarction [19,20]. In addition, it has also been suggested that antioxidant preconditioning could preserve stemness of mesenchymal stem cells [21, trypsin-EDTA (Gibco, USA) and passaged at a ratio of 1:3.…”
mentioning
confidence: 99%
“…Ma et al suggested the usage of melatonin, which is a powerful endogenous antioxidant, for protecting cells against oxidative stress. 44 In order to increase the effectiveness of this antioxidant, the authors developed a technique for melatonin encapsulation in PLGA-mPEG nanoparticles (Mel-NPs). They observed that Mel-NPs achieved a higher melatonin bioactivity index over time and a better therapeutic effect than a conventional melatonin preparation in the model of rat myocardial infarction.…”
Section: Carbon-based Nps Nanotubesmentioning
confidence: 99%
“…They observed that Mel-NPs achieved a higher melatonin bioactivity index over time and a better therapeutic effect than a conventional melatonin preparation in the model of rat myocardial infarction. 44 Myocardial infarction therapy using PLGA NPs was also proposed by Nakano et al 45 who developed bioabsorbable irbesartan-loaded PLGA NPs. The efficacy of irbesartan-NPs was studied in the model of ischemia-reperfusion injury in the mouse heart, showing that such NPs may affect the limitation of infarct size.…”
Section: Carbon-based Nps Nanotubesmentioning
confidence: 99%
“…Unfortunately, the activity of these compounds can deteriorate under physiological conditions, thereby negating their therapeutic value. Now, researchers from the laboratory of Yundai Chen and Feng Cao (Chinese PLA General Hospital, Beijing, People's Republic of China) have developed a means of protecting melatonin and enhancing stem cell‐mediated cardiac repair . In their S tem C ells study, Dong et al discovered that encapsulation within a polymeric nanoparticle both protected melatonin from degradation and permitted controlled melatonin release.…”
Section: Featured Articlesmentioning
confidence: 99%